Facing up to the History of Emotions
V, 136 p.
Keywords: This book brings together several strands of medieval and medievalist work in the history of emotions, with a focus on literary, historical and cinema studies. It asks how we may best ‘face up’ to work that has been done already in these fields, and speculates about work that might yet be done, especially by medievalists working across medieval and postmedieval sources. In the idiom ‘facing up,’ its editors evoke the impulse to assess and realize the place of medieval studies in the burgeoning field of emotions research. Conceptually, psychologically, and artistically, the face is perceived as being at the forefront of many human interactions and emotional practices – as such, the face is not only a powerful conceptual site for theorizing human relationships, past and present, or a site for the representation of emotion: it is itself a catalyst for feeling. As such, the contributions gathered here provide a cutting-edge reflection on the history of medieval emotions. Previously published in postmedieval Volume 8, issue 1, February 2017. Stephanie Downes is Lecturer at La Trobe University, Australia. Stephanie Trigg is Redmond Barry Distinguished Professor at the University of Melbourne, Australia.